2022
DOI: 10.1155/2022/6495301
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Biological Significances of a Ferroptosis-Related Gene Signature in Lung Cancer Based on Deep Learning

Abstract: Acyl-CoA synthetase long-chain family member 4 (ACSL4) has been linked to the occurrence of tumors and is implicated in the ferroptosis process. Deep learning has been applied to many areas in health care, including imaging diagnosis, digital pathology, classification of cancer, and prediction of metastasis. Nonetheless, neither the level of ACSL4 expression nor its predictive significance in non-small-cell lung cancer (NSCLC) is well understood at this time. Predictions of the ACSL4 mRNA expressions in NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, ACSL4 was positively correlated with erastin-induced ferroptosis in NSCLC cells [ 96 ]. When ACSL4 is upregulated, lipid peroxidation products and lethal reactive oxygen species accumulate, thus sensitiating lung cancer cells to ferroptosis [ 97 , 98 ]. Therefore, targeting ACSL4 is an effective way to promote ferroptosis in lung cancer.…”
Section: Targets Of Ferroptosis In Lung Cancermentioning
confidence: 99%
“…In addition, ACSL4 was positively correlated with erastin-induced ferroptosis in NSCLC cells [ 96 ]. When ACSL4 is upregulated, lipid peroxidation products and lethal reactive oxygen species accumulate, thus sensitiating lung cancer cells to ferroptosis [ 97 , 98 ]. Therefore, targeting ACSL4 is an effective way to promote ferroptosis in lung cancer.…”
Section: Targets Of Ferroptosis In Lung Cancermentioning
confidence: 99%
“…Deep learning (unspecified/generic) [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] This category encompasses general deep learning approaches, which may include a variety of architectures and techniques. These approaches often involve several minor modifications or adaptations to cater to the specificities of the task at hand, without specializing in a particular method or model like the other categories.…”
Section: Deep Learning Category Brief Descriptionmentioning
confidence: 99%
“…Del Carmen et al [105] identified chromosomal region alterations associated with therapy response in rectal cancer, utilizing a deep-learning-based algorithm for disease-free survival and overall survival prediction. Huang et al [106] explored the roles of immune microenvironment-related elements in hepatitis B virus-related diseases, while Yang et al [107] investigated the role of ACSL4 in non-small cell lung cancer. The studies underline the ability of deep learning to reveal the intricate links between genetic aberrations and cancer prognosis, further enhancing our understanding of the disease's complex mechanisms.…”
Section: Wang Et Al [109]mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%